2013
DOI: 10.1016/j.msea.2012.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Load partitioning and evidence of deformation twinning in dual-phase fine-grained Zr–2.5%Nb alloy

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. a b s t r a c tIn situ neutron diffraction loading experiments were carried out on a cold-rolled dual-phase (a-phase, $ 10% b-phase) Zr-2.5%Nb alloy at room temperature. The specimens were cut at different angles from the rolling direction (RD) towards the transverse direction (TD), thus the loading axis changes gradually from the rolling to transverse directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the study done by Cai [32] on a hot rolled Zre2.5Nb alloy with weak texture, no twinning activity was found for loading along all three principal directions of the plate under both tensile and compressive tests to about 10% total strain. In comparison Muransky [33] did see twinning during loading of a more strongly textured Zre2.5Nb plate material; it was concluded that the weak texture of the alloy used by Cai meant only a few grains were appropriately oriented for twinning and hence never reached local conditions sufficient to initiate twin formation.…”
Section: Deformation Behavior Of Non-irradiated Zre25nb Pressure Tubementioning
confidence: 97%
See 1 more Smart Citation
“…In the study done by Cai [32] on a hot rolled Zre2.5Nb alloy with weak texture, no twinning activity was found for loading along all three principal directions of the plate under both tensile and compressive tests to about 10% total strain. In comparison Muransky [33] did see twinning during loading of a more strongly textured Zre2.5Nb plate material; it was concluded that the weak texture of the alloy used by Cai meant only a few grains were appropriately oriented for twinning and hence never reached local conditions sufficient to initiate twin formation.…”
Section: Deformation Behavior Of Non-irradiated Zre25nb Pressure Tubementioning
confidence: 97%
“…Hence only the lattice strains of the a phase are reported. Previous studies of pressure tube Zre2.5Nb have shown that the b phase has a higher strength than the a, and the strength of the a phase is what principally controls the strength of ZreNb two phase alloy [32,33]. Therefore through studying the evolution of lattice strains for different grain families in the alpha phase we will be able to obtain an understanding of the dominant factors controlling the deformation behavior of Zre2.5Nb pressure tube material with and without fast neutron irradiation.…”
Section: Lattice Strain Developmentmentioning
confidence: 99%
“…At a larger http scale, a comprehensive 2D statistical study of grain size, orientation, and boundary lengths on twin nucleation in Zr and Mg samples was given by Capolungo et al [16] and Beyerlein et al [17], respectively, using ElectronBackscattered Diffraction (EBSD). Also, neutron diffraction measurements have revealed that stresses in some measured directions are relaxed in newly born twins in comparison to their parent grains [18,19]. Although neutron diffraction provides a good statistical picture of interaction between all twin and parent grains, the stress tensor within each twin and its specific parent grain has not yet been measured statistically.…”
Section: Introductionmentioning
confidence: 99%
“…However, the information retrieved from the OM, SEM, EBSD, and TEM are constrained to the sample surface or thin film. Previous research also used in-situ neutron diffraction (Withers and Clarke, 1998;Gharghouri et al, 1999;Brown et al, 2005a;Brown et al, 2005b;Davies et al, 2005;Clausen et al, 2008;Muranskya et al, 2008;Woo et al, 2008;Hao et al, 2009;Muransky et al, 2009;Muransky et al, 2010;Abdolvand and Daymond, 2012;Balogh et al, 2012;Brown et al, 2013a;Brown et al, 2013b;Muransky et al, 2013;Prakash et al, 2013;Skippon et al, 2013;) to investigate the deformation mechanisms of Mg alloys and other HCPstructured materials during discontinuous step-loading. The different dominant deformation modes were successfully distinguished from the perspective of diffraction, when Mg alloys were subjected to the initial texture and strain-path changes.…”
Section: Introductionmentioning
confidence: 99%